LncRNA SNHG7 sponges miR‐425 to promote proliferation, migration, and invasion of hepatic carcinoma cells via Wnt/β‐catenin/EMT signalling pathway. (2nd September 2019) - Yao, Xuebing; Liu, Chi; Liu, Cuiyun; Xi, Wenna; Sun, Shuilin; Gao, Zhen
Abstract : Increasing evidence has indicated the important roles of long noncoding RNA small nucleolar RNA host gene 7 (SNHG7) in tumourigenesis as a potential oncogene. However, the function of SNHG7 in hepatic carcinoma remains unclear. In the present study, we found that SNHG7 expression was significantly upregulated in hepatic carcinoma tissues, especially in aggressive cases, and it was closely correlated with the poor prognosis. Furthermore, knockdown of SNHG7 inhibited the proliferation, migration, and invasion of hepatic carcinoma cell lines in vitro. Mechanistically, SNHG7 directly interacted with miR‐425 as a ceRNA. Moreover, knockdown of SNHG7 significantly inhibited the tumorigenic Wnt/β‐catenin/EMT pathway. SNHG7 regulated Wnt/β‐catenin/EMT pathway through sponging miR‐425 and played an oncogenic role in hepatic carcinoma progression. Together, our study elucidated the role of SNHG7 as a ceRNA in hepatic carcinoma, provided new potential diagnosis and therapeutic application in hepatic carcinoma progression. Significance of the study: SNHG7 could promote proliferation and metastasis of hepatic carcinoma cell in vitro and in vivo, suggesting that SNHG7 exerts tumorigenic role in hepatic carcinoma progression. Further mechanism research revealed that SNHG7 exhibited the tumorigenic role through Wnt/β‐catenin/EMT pathway as a miR‐425 sponge. These findings provided new cues to understand the molecular signalling network in carcinogenesis of hepatic carcinoma, and it may provide new evidence for therapeutic application in hepatic carcinoma.